Evaluation of ferrous benzoic methylthymol-blue gel as a dosimeter via magnetic resonance imaging. (December 2020) - Parwaie, Wrya; Geraily, Ghazale; Shirazi, Alireza; Mehri-Kakavand, Ghazal; Farzin, Mostafa
Highlights: R2 dose–response shows a higher sensitivity compared to R1 dose–response. A notable dependence on scanning temperature was observed at higher doses. R1 and R2 increased significantly immediately to 1.5 h' post-irradiation. Abstract: Purpose: In previous studies, methylthymol-blue and benzoic acid have been introduced as a diffuser limiter and sensitivity enhancer in the gel dosimeter composition, respectively. This work focused on analyzing a formulation of the Fricke gel dosimeter consisting of methylthymol-blue and benzoic acid through magnetic resonance imaging. Methods: The gel dosimeter samples were irradiated using 6, 10, and 15 MV photons with different levels of doses and read using a 1.5 T scanner in order to evaluate the dose–response sensitivity and to study the effect of benzoic acid concentration, diffusion coefficient and temperature and to determine the temporal stability of the gel dosimeter. Results: Inspection of radiological properties revealed that this gel dosimeter can be considered as a tissue equivalent medium. Within the dose range 0 to 1000 cGy, the R1 sensitivity and R2 sensitivity of the gel dosimeter equaled 0.058 ± 0.003 and 0.092 ± 0.004 s −1 Gy −1, respectively. The diffusion coefficient was less than 0.85 ± 0.02mm 2 h −1 for doses higher than 200 cGy. In addition, by changing the temperature from 15C to 25, the R1 sensitivity and R2 sensitivity decreased about 5 and 11%, respectively. Further, no significant energy and dose rate dependence were observed over photon energies of 6, 10, and 15 MV and over the range 65 to 525 cGy min −1 . Conclusions: Based on our observation, the ferrous benzoic acid methylthymol-blue gel dosimeter can be suggested to measure the dose distribution. Further analysis is required to clarify its performance in clinical situations.